MEDIATING EFFECT OF INTERNAL AUDITORS’ ETHICAL CONDUCT ON THE RELATIONSHIP BETWEEN USAGE OF INFORMATION TECHNOLOGY, MANAGEMENT SUPPORT FOR INTERNAL AUDIT DEPARTMENT, AND INTERNAL AUDIT EFFECTIVENESS: A CONCEPTUAL FRAMEWORK - Nura Badamasi; Adura Binti Ahmad (Gusau Journal of Accounting and Finance, 2024)
Low level of internal audit effectiveness is practically increasing in the Nigerian ministries, department, and agencies. In proffering solution to this lingering issue, this present study proposed a framework to examine the degree of effectiveness of internal audit functions in Kano state, Nigeria MDAs. The proposed framework is motivated by agency theory with the mediating effect of auditor’s ethical conduct. This present study extends the already extant body of knowledge in the area of internal audit effectiveness by expanding agency theory with the mediating effect of auditor’s ethical conduct. Also, this study has implication to support management, shareholders and other policy makers in addressing ineffectiveness and corrupt practices in the Nigerian MDAs. If this framework is authenticated, it would provide more evocative insight on the extends of internal audit effectiveness in Kano Nigerian MDAs, the legislators and government official would benefit greatly from this study if eventually concluded as it would assist MDAs to enhance internal audit effectiveness and curb corruption. In the subsequent studies the proposed framework will be empirically tested through data collection and analysis of relevant data.